Dividend Payout and Distance to Default of Listed Companies in Bursa Malaysia - Khan, Owais (Universiti Malaysia Sarawak (UNIMAS), 2019)
Bonds and dividend payout have become an extensively accepted measure of a firm’s business risk, and it is considered as an important issue in firms. The goal of this study is the corporate bonds' distance to default (DtD) for firms listed on the Bursa Malaysia, founded on data obtained from 297 issuing firms during ten years period from 2006 to 2015. In this study, the factors of dividends payout on bonds in the Malaysian sectors are investigated on the base of agency theory and signalling theory. This study employs the stata panel estimator for the experimental testing of the hypothesis that can investigate the financial behaviour of the firms. This study has used Bharath and Shumway (2008) DtD mixtures model, combining both accounting and market-based evidence to unravel the Malaysian corporate bonds DtD quality. The independent variable, dividends Payout, is the measure to check its relationship on distance to default (bonds). In addition, three control variables, leverage (lev), equity beta (eβ) and market to book (mtb) are examined to evaluate their influence on the Malaysian corporate bonds’ riskiness. The results indicated that dividends payout have significant and positive relationship on the distance to default (DtD) (bonds). Additionally, three controlled variables lev, mtb and eβ, the two control variables lev and mtb and eβ significant effect on DtD. Keywords: Distance to default, bonds, dividend payout, Bursa Malaysia, leverage, Market to Book, Equity Beta.